Optimising RAPD-PCR for Screening the Link of RAPD Markers to an Acid-resistant Gene in Oenococcus oeni - Liu, S.; He, L.; Li, X.; Li, X. (South African Journal of Enology and Viticulture, 2011)
RAPD-PCR conditions were optimised for screening RAPD markers linked to the acid-resistant gene in Oenococcus oeni. Two (S40, S333) out of 45 random primers were capable of producing stable polymorphism in O. oeni isolates. Thirty-three acid-resistant isolates and nine acid-sensitive isolates of O. oeni were used for screening RAPD markers linked to the acid-resistant gene. Specific bands of S40-1400 and S333-650 were amplified in 31 (94%) and 33 (100%) of 33 acid-resistant O. oeni isolates. The optimised RAPD-PCR method can potentially be used for the fast screening of acid-resistant O. oeni strains.